Corrigendum to “Managing recreational fisheries from a multi-species perspective: Leveraging species interactions and accounting for positive feedback loops to maintain desired ecosystem states” [Fish. Res. 300 (August) (2026) 107807] - Colin J. Dassow; Chelsey L. Nieman; Christopher T. Solomon; Greg G. Sass; Stuart E. Jones (Fisheries Research, 2026)

Managing recreational fisheries from a multi-species perspective: Leveraging species interactions and accounting for positive feedback loops to maintain desired ecosystem states - Colin J. Dassow; Chelsey L. Nieman; Christopher T. Solomon; Greg G. Sass; Stuart E. Jones (Fisheries Research, 2026)

The Scotland–Canada overturning array (SCOTIA): twenty years of meridional overturning in the subpolar North Atlantic - Alan D. Fox; Neil J. Fraser; Kristin Burmeister; Sam C. Jones; Stuart A. Cunningham; Lewis A. Drysdale; Ahmad Fehmi Dilmahamod; Johannes Karstensen (Ocean Science, 2026)
The Atlantic meridional overturning circulation (AMOC) is expected to decline dramatically over the 21st century, with severe impacts for Northern Hemisphere climate. After 20 years of sustained monitoring in the subtropics, a detectable AMOC weakening trend is now beginning to emerge. However, continuous observations at subpolar latitudes are currently too short-lived to determine any weakening signal above the large-amplitude interannual variability. Here, we introduce a new subpolar observing configuration, SCOTIA (Scotland–Canada overturning array), combining parts of the existing OSNAP mooring array with scattered CTD and Argo data, to extend the record of subpolar AMOC backward in time to cover the subtropical monitoring period, 2004–2024. SCOTIA facilitates a rigorous comparison of the decadal-scale variability in transports and overturning at subpolar and subtropical latitudes. Our results show subpolar AMOC varies on pentadal to decadal timescales with an amplitude comparable to that observed in the subtropics. Anomalously high overturning during 2016–2020 was driven by increased southward transports in the density classes associated with Labrador Sea Water. We find no statistically significant trend in subpolar AMOC during the period 2004–2024.

Improving spine‐based age estimation in centrarchid fishes using otolith‐derived training sets - Matthew P. Woo; Stuart E. Jones; Brian S. Ankrapp; Avi Neumann; Julián Torres‐Dowdall (Journal of Fish Biology, 2026)
Nonlethal age determination is a priority in fish biology contexts where sacrifice is restricted, but estimates derived from nonlethally attainable structures tend to suffer from poor precision and accuracy relative to necessarily lethal, otolith‐derived estimates. Dorsal spines, while less accurate than otoliths, have shown higher precision compared to other alternative structures, making them a useful candidate for testing reader‐based approaches to improved age estimation. Here, we test whether small, lake‐specific training sets derived from paired otolith‐spine images, derived from incidental mortalities can provide useful calibration to spine‐based age estimates in four centrarchid populations from the northern Midwest, including two largemouth bass ( Micropterus nigricans ) and two bluegill ( Lepomis macrochirus ) populations. Five moderately experienced readers estimated ages from spine images before and after calibration with paired otolith‐spine images. Calibration consistently resulted in increased estimated ages, particularly for older fish, and reduced variability among readers in both individual age estimates and predicted length‐at‐age trajectories. Specifically, we find that these structured training sets are useful in both reducing traditional underestimation biases and reducing reader‐based variance effects at both the level of individual estimates and in growth modelling contexts. Therefore, they may offer a practical means of leveraging available incidental mortalities in the improvement of otherwise nonlethal aging programs. Accordingly, we suggest that where available, readers first be familiarized with lake‐specific paired otolith‐spine images before independently estimating spine ages.

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Conservation changed but not divided - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Amy Hinsley; Sadiq Jaffer; et al. (Trends in Ecology & Evolution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

More than the sum of their parts — Environmental flows increase fish movement and fishway functionality - Matthew Jones; Paul Moloney; Robin Hale; Ivor Stuart; Justin O'Connor; Zeb Tonkin (Ecological Engineering, 2025)

A review and discussion on the influences of grain-coating clay minerals on water-rock interactions in sandstones - Huan Li; Qinhong Hu; Stuart Jones; Jon Gluyas; Eric O. Ansah; Saju Menacherry; Qiqi Wang; Tao Ye (Earth-Science Reviews, 2025)

Robust Sensory Traits Across Light Habitats: Visual Signals but Not Receptors Vary in Centrarchids Inhabiting Distinct Photic Environments - César Bertinetti; Camille Mosley; Stuart Jones; Julián Torres‐Dowdall (Molecular Ecology, 2025)
Visual communication in fish is often shaped by their light environment, which influences both sensory (e.g., eye size, opsin gene expression) and signalling traits (e.g., body reflectance). This study explores the phenotypic variation in the visual communication traits of six species of centrarchids (Centrarchidae) inhabiting two contrasting light environments. We measured morphological, molecular and signalling traits to determine their variation across photic conditions. Our findings reveal significant interspecific variation in sensory traits but no consistent phenotypic variation between light environments. Centrarchids showed robust visual systems with green‐sensitive rh2 and red‐sensitive lws opsin genes representing the main chromatic channels, with their expression remaining largely unaffected between distinct light habitats. We also found significant molecular evolution in the visual opsin genes, although these changes were not associated with environmental conditions. However, body reflectance displayed species‐specific responses to environmental conditions, suggesting that signalling traits may be more flexible than sensory traits. Overall, our results challenge the generality of the current paradigm in visual ecology, which portrays visual systems in fish as highly tunable owing to photic conditions. Our study highlights the potential evolutionary or developmental constraints on centrarchid visual systems and their implications for adaptability to various habitats and novel environmental threats.

The potential for AI to revolutionize conservation: a horizon scan - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Francis Gassert; Amy Hinsley; et al. (Trends in Ecology & Evolution, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Fish and invertebrate communities show greater day–night partitioning on tropical than temperate reefs - Tyson R. Jones; Graham J. Edgar; Rowan Trebilco; Camille Mellin; Rick D. Stuart‐Smith; Lara Denis‐Roy; Olivia J. Johnson; Matthew Rose; Scott D. Ling (Ecology, 2025)
Diel partitioning of animals within ecological communities is widely acknowledged, yet rarely quantified. Investigation of most ecological patterns and processes involves convenient daylight sampling, with little consideration of the contributions of nocturnal taxa, particularly in marine environments. Here we assess diel partitioning of reef faunal assemblages at a continental scale utilizing paired day and night visual census across 54 shallow tropical and temperate reefs around Australia. Day–night differences were most pronounced in the tropics, with fishes and invertebrates displaying distinct and opposing diel occupancy on coral reefs. Tropical reefs in daytime were occupied primarily by fishes not observed at night (64% of all species sighted across day and night, and 71% of all individuals). By night, substantial emergence of invertebrates not otherwise detected during sunlit hours occurred (56% of all species, and 45% of individuals). Nocturnal emergence of tropical invertebrates corresponded with significant declines in the richness and biomass of predatory and herbivorous diurnal fishes. In contrast, relatively small diel changes in fishes active on temperate reefs corresponded to limited nocturnal emergence of temperate invertebrates. This reduced partitioning may, at least in part, be a result of strong top‐down pressures from fishes on invertebrate communities, either by predation or competitive interference. For shallow reefs, the diel cycle triggers distinct emergence and retreat of faunal assemblages and associated trophic patterns and processes, which otherwise go unnoticed during hours of regular scientific monitoring. Improved understanding of reef ecology, and management of reef ecosystems, requires greater consideration of nocturnal interactions. Without explicit sampling of nocturnal patterns and processes, we may be missing up to half of the story when assessing ecological interactions.

Assessing the global prevalence of wild birds in trade - Paul F. Donald; Eresha Fernando; Lauren Brown; Michela Busana; Stuart H. M. Butchart; Serene Chng; Alicia de la Colina; Juliana Machado Ferreira; Anuj Jain; Victoria R. Jones; Rocio Lapido; Kelly Malsch; et al. (Conservation Biology, 2024)
Trade represents a significant threat to many wild species and is often clandestine and poorly monitored. Information on which species are most prevalent in trade and potentially threatened by it therefore remains fragmentary. We used 7 global data sets on birds in trade to identify species or groups of species at particular risk and assessed the extent to which they were congruent in terms of the species recorded in trade. We used the frequency with which species were recorded in the data sets as the basis for a trade prevalence score that was applied to all bird species globally. Literature searches and questionnaire surveys were used to develop a list of species known to be heavily traded to validate the trade prevalence score. The score was modeled to identify significant predictors of trade. Although the data sets sampled different parts of the broad trade spectrum, congruence among them was statistically strong in all comparisons. Furthermore, the frequency with which species were recorded within data sets was positively correlated with their occurrence across data sets, indicating that the trade prevalence score captured information on trade volume. The trade prevalence score discriminated well between species identified from semi‐independent assessments as heavily or unsustainably traded and all other species. Globally, 45.1% of all bird species and 36.7% of globally threatened bird species had trade prevalence scores ≥1. Species listed in Appendices I or II of CITES, species with large geographical distributions, and nonpasserines tended to have high trade prevalence scores. Speciose orders with high mean trade prevalence scores included Falconiformes, Psittaciformes, Accipitriformes, Anseriformes, Bucerotiformes, and Strigiformes. Despite their low mean prevalence score, Passeriformes accounted for the highest overall number of traded species of any order but had low representation in CITES appendices. Geographical hotspots where large numbers of traded species co‐occur differed among passerines (Southeast Asia and Eurasia) and nonpasserines (central South America, sub‐Saharan Africa, and India). This first attempt to quantify and map the relative prevalence in trade of all bird species globally can be used to identify species and groups of species that may be at particular risk of harm from trade and can inform conservation and policy interventions to reduce its adverse impacts.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Lithofacies assemblage and effects on diagenesis in lacustrine tight sandstone reservoirs: Samples from Upper Triassic Yanchang Formation, Ordos Basin, China - Hao Lu; Dali Yue; Stuart J. Jones; Shixiang Li; Wurong Wang; Bin Bai; Xiulin Hou; Zhen Li; Shenghe Wu; Qing Li (Marine and Petroleum Geology, 2024)

Geology of the Utah Frontier Observatory for Research in Geothermal Energy (FORGE) Enhanced Geothermal System (EGS) Site - Clay Jones; Stuart Simmons; Joseph Moore (Geothermics, 2024)

Rock fishways: Natural designs for an engineered world - Ivor G. Stuart; Timothy J. Marsden; Matthew J. Jones; Matt T. Moore; Lee J. Baumgartner (Ecological Engineering, 2024)

Counteracting effects of “hook avoidance” and “hook habituation” on angler catch rates in a catch‐and‐release fishery - Camille L. Mosley; Colin J. Dassow; Christopher T. Solomon; Stuart E. Jones (Fisheries Management and Ecology, 2024)
Catch‐and‐release (C&R) angling is often used to maintain high catch rates but fish vulnerability to capture may decrease following hooking, thereby decreasing angler catch per unit effort (CPUE) (hyperdepletion). To determine if fish post‐capture response affected recapture probability and population‐level CPUE, individual capture histories of Largemouth Bass in two lakes were compared before and after doubling angling effort in a Before‐After Control‐Impact (BACI) analysis. Previous capture and day‐of‐season both affected recapture probability. Counteracting effects of previous capture and reduced late‐season catch rates caused no hyperdepletion of angler CPUE. Our results highlight the complexity of fish behavioral responses to angling and suggest that hyperdepletion of angling catch rates may not be an issue in C&R fisheries.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Modelling mastication and aroma release from white rice during food oral processing - Syahmeer How; Jim R. Jones; Marco P. Morgenstern; Eli Gray-Stuart; John E. Bronlund; Anne Saint-Eve; Ioan Cristian Trelea; Isabelle Souchon (Journal of Food Engineering, 2023)

Enrollment, retention, and inclusivity of Marine Stewardship Council (MSC) eco-labelling certifications - Stuart T. Jones; Edward H. Allison; Kailin Kroetz; Yoshitaka Ota; Sunny L. Jardine (Marine Policy, 2023)

Molecular complexity and diversity of persistent soil organic matter - Andrew R. Jones; Ram C. Dalal; Vadakattu V.S.R. Gupta; Susanne Schmidt; Diane E. Allen; Geraldine E. Jacobsen; Michael Bird; A. Stuart Grandy; Jonathan Sanderman (Soil Biology and Biochemistry, 2023)

Conceptualising social licence to operate - Alice Stuart; Alan Bond; Aldina M.A. Franco; Julia Baker; Chris Gerrard; Vittoria Danino; Kylie Jones (Resources Policy, 2023)

Geophysical reconstruction of the late Holocene proximal proglacial landsystem at Skeiðarársandur, southeast Iceland - Devin Harrison; Neil Ross; Andrew J. Russell; Stuart J. Jones (Journal of Quaternary Science, 2023)
Sandur plains are extensive sedimentary bodies formed in proglacial settings by glaciofluvial processes. Icelandic sandar have been hypothesised to be comprised of thick alluvial successions that provide critical insight into the processes that contributed to their formation and evolution. However, to‐date, most sandar research has focused on the analysis of sedimentary successions associated to topographically‐confined and small‐scale systems. These, however, do not capture the variety or scale of processes that influence sandar architecture. Therefore, detailed subsurface analysis of large‐scale and unconfined sandar is vital to understand how these systems respond to fundamental drivers, such as: (i) glacier oscillations, and (ii) episodic sediment flux from glacier outburst floods (aka. jökulhlaups). We report an extensive, low‐frequency (40 & 100 MHz) ground‐penetrating radar (GPR) survey of the ice‐proximal component of a large‐scale () active sandur in southeast Iceland. A bright and continuous reflection (PR1) is identified within all radargrams and provides a boundary between pre‐LIA and LIA to present‐day sedimentation. GPR data reveals a ~50 m thick ice‐proximal sediment wedge that is attributed to jökulhlaup and surge‐related glaciofluvial activity during the Little Ice Age (LIA). An approximate rate of deposition of 0.2–0.65 m has been calculated for the sediment wedge above PR1. Furthermore, we propose an extensive, sandur‐wide, pre‐LIA ice marginal limit of Skeiðarárökull, southeast Iceland, based on observations reported here and in previous work.

Depensation in fish recruitment driven by context-dependent interactions with another predator - Colin Dassow; Greg Sass; Stephanie Shaw; Zachary Feiner; Chelsey Nieman; Stuart Jones (Fisheries Research, 2023)

Understanding the effect of metamictization on the efficiency of zircon milling - Matthew J. Smith; Emma Jones; Stuart Blackburn; Richard W. Greenwood (Minerals Engineering, 2023)

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Introducing a common taxonomy to support learning from failure in conservation - Iain Dickson; Stuart H. M. Butchart; Allison Catalano; David Gibbons; Julia P. G. Jones; Katie Lee‐Brooks; Thomasina Oldfield; David Noble; Stuart Paterson; Sugoto Roy; Julien Semelin; Paul Tinsley‐Marshall; et al. (Conservation Biology, 2023)
Although some sectors have made significant progress in learning from failure, there is currently limited consensus on how a similar transition could best be achieved in conservation and what is required to facilitate this. One of the key enabling conditions for other sectors is a widely accepted and standardized classification system for identifying and analyzing root causes of failure. We devised a comprehensive taxonomy of root causes of failure affecting conservation projects. To develop this, we solicited examples of real‐life conservation efforts that were deemed to have failed in some way, identified their underlying root causes of failure, and used these to develop a generic, 3‐tier taxonomy of the ways in which projects fail, at the top of which are 6 overarching cause categories that are further divided into midlevel cause categories and specific root causes. We tested the taxonomy by asking conservation practitioners to use it to classify the causes of failure for conservation efforts they had been involved in. No significant gaps or redundancies were identified during this testing phase. We then analyzed the frequency that particular root causes were encountered by projects within this test sample, which suggested that some root causes were more likely to be encountered than others and that a small number of root causes were more likely to be encountered by projects implementing particular types of conservation action. Our taxonomy could be used to improve identification, analysis, and subsequent learning from failed conservation efforts, address some of the barriers that currently limit the ability of conservation practitioners to learn from failure, and contribute to establishing an effective culture of learning from failure within conservation.

Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - João L. Guilherme; Victoria R. Jones; Inês Catry; Martin Beal; Maria P. Dias; Steffen Oppel; Juliet A. Vickery; Chris M. Hewson; Stuart H. M. Butchart; Ana S. L. Rodrigues (Conservation Biology, 2023)
The conservation of long‐distance migratory birds requires coordination between the multiple countries connected by the movements of these species. The recent expansion of tracking studies is shedding new light on these movements, but much of this information is fragmented and inaccessible to conservation practitioners and policy makers. We synthesized current knowledge on the connectivity established between countries by landbirds and raptors migrating along the African–Eurasian flyway. We reviewed tracking studies to compile migration records for 1229 individual birds, from which we derived 544 migratory links, each link corresponding to a species’ connection between a breeding country in Europe and a nonbreeding country in sub‐Saharan Africa. We used these migratory links to analyze trends in knowledge over time and spatial patterns of connectivity per country (across species), per species (across countries), and at the flyway scale (across all countries and all species). The number of tracking studies available increased steadily since 2010 (particularly for landbirds), but the coverage of existing tracking data was highly incomplete. An average of 7.5% of migratory landbird species and 14.6% of raptor species were tracked per country. More data existed from central and western European countries, and it was biased toward larger bodied species. We provide species‐ and country‐level syntheses of the migratory links we identified from the reviewed studies, involving 123 populations of 43 species, migrating between 28 European and 43 African countries. Several countries (e.g., Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for future tracking studies to complement existing data, particularly on landbirds. Despite the limitations in existing tracking data, our data and results can inform discussions under 2 key policy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia.

In-Silico Modelling of Transdermal Delivery of Macromolecule Drugs Assisted by a Skin Stretching Hypobaric Device - Daniel Sebastia-Saez; Faiza Benaouda; Chui Hua Lim; Guoping Lian; Stuart A. Jones; Liang Cui; Tao Chen (Pharmaceutical Research, 2023)
Objectives To develop a simulation model to explore the interplay between mechanical stretch and diffusion of large molecules into the skin under locally applied hypobaric pressure, a novel penetration enhancement method. Methods Finite element method was used to model the skin mechanical deformation and molecular diffusion processes, with validation against in-vitro transdermal permeation experiments. Simulations and experimental data were used together to investigate the transdermal permeation of large molecules under local hypobaric pressure. Results Mechanical simulations resulted in skin stretching and thinning (20%–26% hair follicle diameter increase, and 21%–27% skin thickness reduction). Concentration of dextrans in the stratum corneum was below detection limit with and without hypobaric pressure. Concentrations in viable epidermis and dermis were not affected by hypobaric pressure (approximately 2 μg $$\bullet$$ ∙ cm −2 ). Permeation into the receptor fluid was substantially enhanced from below the detection limit at atmospheric pressure to up to 6 μg $$\bullet$$ ∙ cm −2 under hypobaric pressure. The in-silico simulations compared satisfactorily with the experimental results at atmospheric conditions. Under hypobaric pressure, satisfactory comparison was attained when the diffusion coefficients of dextrans in the skin layers were increased from $$\sim$$ ∼ 10 μm 2 $$\bullet$$ ∙ s −1 to between 200–500 μm 2 $$\bullet$$ ∙ s −1 . Conclusions Application of hypobaric pressure induces skin mechanical stretching and enlarges the hair follicle. This enlargement alone cannot satisfactorily explain the increased transdermal permeation into the receptor fluid under hypobaric pressure. The results from the in-silico simulations suggest that the application of hypobaric pressure increases diffusion in the skin, which leads to improved overall transdermal permeation.

Hydrologic Setting Dictates the Sensitivity of Ecosystem Metabolism to Climate Variability in Lakes - Isabella A. Oleksy; Stuart E. Jones; Christopher T. Solomon (Ecosystems, 2022)
Global change is influencing production and respiration in ecosystems across the globe. Lakes in particular are changing in response to climatic variability and cultural eutrophication, resulting in changes in ecosystem metabolism. Although the primary drivers of production and respiration such as the availability of nutrients, light, and carbon are well known, heterogeneity in hydrologic setting (for example, hydrological connectivity, morphometry, and residence) across and within regions may lead to highly variable responses to the same drivers of change, complicating our efforts to predict these responses. We explored how differences in hydrologic setting among lakes influenced spatial and inter annual variability in ecosystem metabolism, using high-frequency oxygen sensor data from 11 lakes over 8 years. Trends in mean metabolic rates of lakes generally followed gradients of nutrient and carbon concentrations, which were lowest in seepage lakes, followed by drainage lakes, and higher in bog lakes. We found that while ecosystem respiration (ER) was consistently higher in wet years in all hydrologic settings, gross primary production (GPP) only increased in tandem in drainage lakes. However, interannual rates of ER and GPP were relatively stable in drainage lakes, in contrast to seepage and bog lakes which had coefficients of variation in metabolism between 22–32%. We explored how the geospatial context of lakes, including hydrologic residence time, watershed area to lake area, and landscape position influenced the sensitivity of individual lake responses to climatic variation. We propose a conceptual framework to help steer future investigations of how hydrologic setting mediates the response of metabolism to climatic variability.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pond methane dynamics, from microbial communities to ecosystem budget, during summer in Alaska - Carmella Vizza; Stuart E. Jones; Julia A. Hart; William E. West; Gary A. Lamberti (Limnology and Oceanography, 2022)
Ponds play a larger role in the global freshwater methane (CH 4 ) budget than predicted from surface area alone. To improve our understanding of pond CH 4 dynamics, we measured summer CH 4 production, concentrations, and emissions to the atmosphere in nine Alaskan wetland ponds along with potential physical, chemical, and biological regulators. Pond CH 4 production (0.64, 0.086–1.3 mmol m −2 d −1 ; median, interquartile range), as assessed with slurry incubations, was positively related to water‐column temperature and chlorophyll a (Chl a ), negatively influenced by oxygen levels, and varied with microbial community structure. Average water‐column CH 4 concentrations (0.39, 0.21–0.87 μ mol L −1 ) were lower in deeper ponds and at higher oxygen levels, and as expected, they were correlated with diffusive emissions (0.055, 0.024–0.20 mmol m −2 d −1 ) assessed with flux chambers. Based on a mass balance approach, 39–99% of CH 4 produced in ponds was oxidized. Pond ebullition (3.7, 0.60–24 mmol m −2 d −1 ) was higher and more variable than diffusive emissions. Additionally, pond ebullition rates were better correlated with production rates from the previous month. We also systematically compared the ratio of ebullition to diffusive CH 4 emissions in our ponds and other northern lakes, which was negatively related to water depth ( n = 71), but positively related to Chl a (n = 28). Our study sheds light on the factors that influence pond CH 4 dynamics and demonstrates that pond ebullition is a significant CH 4 source worthy of continued study.

Setting priorities for climate change adaptation of Critical Sites in the Africa‐Eurasian waterbird flyways - Frank T. Breiner; Mira Anand; Stuart H. M. Butchart; Martina Flörke; Etienne Fluet‐Chouinard; Antoine Guisan; Lammert Hilarides; Victoria R. Jones; Mikhail Kalyakin; Bernhard Lehner; Merijn van Leeuwen; James W. Pearce‐Higgins; et al. (Global Change Biology, 2022)
Despite their importance for biodiversity and ecosystem services, wetlands are among the most threatened ecosystems globally. The conservation of many migratory waterbirds depends on the conservation of a network of key sites along their flyways. However, the suitability of these sites is changing under climate change, and it is important that management of individual sites in the network adapts to these changes. Using bioclimatic models that also account for changes in inundation, we found that projected climate change will reduce habitat suitability for waterbirds at 57.5% of existing Critical Sites within Africa‐Eurasia, varying from 20.1% in Eastern Europe to 87.0% in Africa. African and Middle East sites are particularly threatened, comprising 71 of the 100 most vulnerable sites. By highlighting priority sites for conservation and classifying Critical Sites into Climate Change Adaptation Strategy (CCAS) classes, our results can be used to support the climate change adaptation of both individual sites and the entire site network.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

The value of local community knowledge in species distribution modelling for a threatened Neotropical parrot - Rebecca Biddle; Ivette Solis-Ponce; Martin Jones; Stuart Marsden; Mark Pilgrim; Christian Devenish (Biodiversity and Conservation, 2021)
Species distribution models are widely used in conservation planning, but obtaining the necessary occurrence data can be challenging, particularly for rare species. In these cases, citizen science may provide insight into species distributions. To understand the distribution of the newly described and Critically Endangered Amazona lilacina, we collated species observations and reliable eBird records from 2010–2020. We combined these with environmental predictors and either randomly generated background points or absence points generated from eBird checklists, to build distribution models using MaxEnt. We also conducted interviews with people local to the species’ range to gather community-sourced occurrence data. We grouped these data according to perceived expertise of the observer, based on the ability to identify A. lilacina and its distinguishing features, knowledge of its ecology, overall awareness of parrot biodiversity, and the observation type. We evaluated all models using AUC and Tjur R 2 . Field data models built using background points performed better than those using eBird absence points (AUC = 0.80 ± 0.02, Tjur R 2 = 0.46 ± 0.01 compared to AUC = 0.78 ± 0.03, Tjur R 2 = 0.43 ± 0.21). The best performing community data model used presence records from people who were able recognise a photograph of A. lilacina and correctly describe its distinguishing physical or behavioural characteristics (AUC = 0.84 ± 0.05, Tjur R 2 = 0.51± 0.01). There was up to 92% overlap between the field data and community data models, which when combined, predicted 17,772 km 2 of suitable habitat. Use of community knowledge offers a cost-efficient method to obtain data for species distribution modelling; we offer recommendations on how to assess its performance and present a final map of potential distribution for A. lilacina.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

A Multi-Model Pipeline for Translational Intracerebral Haemorrhage Research - Sarah E. Withers; Adrian R. Parry-Jones; Stuart M. Allan; Paul R. Kasher (Translational Stroke Research, 2020)
Apart from acute and chronic blood pressure lowering, we have no specific medications to prevent intracerebral haemorrhage (ICH) or improve outcomes once bleeding has occurred. One reason for this may be related to particular limitations associated with the current pre-clinical models of ICH, leading to a failure to translate into the clinic. It would seem that a breakdown in the ‘drug development pipeline’ currently exists for translational ICH research which needs to be urgently addressed. Here, we review the most commonly used pre-clinical models of ICH and discuss their advantages and disadvantages in the context of translational studies. We propose that to increase our chances of successfully identifying new therapeutics for ICH, a bi-directional, 2- or 3-pronged approach using more than one model species/system could be useful for confirming key pre-clinical observations. Furthermore, we highlight that post-mortem/ex-vivo ICH patient material is a precious and underused resource which could play an essential role in the verification of experimental results prior to consideration for further clinical investigation. Embracing multidisciplinary collaboration between pre-clinical and clinical ICH research groups will be essential to ensure the success of this type of approach in the future.

Coexistence barriers confine the poleward range of a globally distributed plant - David W. Armitage; Stuart E. Jones (Ecology Letters, 2020)
In the study of factors shaping species' poleward range boundaries, climatic constraints are often assigned greater importance than biotic interactions such as competition. However, theory suggests competition can truncate a species' fundamental niche in harsh environments. We test this by challenging a mechanistic niche model – containing explicit competition terms – to predict the poleward range boundaries of two globally distributed, ecologically similar aquatic plant species. Mechanistic competition models accurately predicted the northern range limits of our study species, outperforming competition‐free mechanistic models and matching the predictive ability of statistical niche models fit to occurrence records. Using the framework of modern coexistence theory, we found that relative nonlinearity in competitors' responses to temperature fluctuations maintains their coexistence boundary, highlighting the importance of this fluctuation‐dependent mechanism. Our results support a more nuanced, interactive role of climate and competition in determining range boundaries, and illustrate a practical, process‐based approach to understanding the determinants of range limits.

Shifting limitation of primary production: experimental support for a new model in lake ecosystems - Carly R. Olson; Christopher T. Solomon; Stuart E. Jones (Ecology Letters, 2020)
The limits on primary production vary in complex ways across space and time. Strong tests of clear conceptual models have been instrumental in understanding these patterns in both terrestrial and aquatic ecosystems. Here we present the first experimental test of a new model describing how shifts from nutrient to light limitation control primary productivity in lake ecosystems as hydrological inputs of nutrients and organic matter vary. We found support for two key predictions of the model: that gross primary production (GPP) follows a hump‐shaped relationship with increasing dissolved organic carbon (DOC) concentrations; and that the maximum GPP, and the critical DOC concentration at which the hump occurs, are determined by the stoichiometry and chromophoricity of the hydrological inputs. Our results advance fundamental understanding of the limits on aquatic primary production, and have important applications given ongoing anthropogenic alterations of the nutrient and organic matter inputs to surface waters.

Frontiers in modelling social–ecological dynamics of recreational fisheries: A review and synthesis - Christopher T. Solomon; Colin J. Dassow; Carolyn M. Iwicki; Olaf P. Jensen; Stuart E. Jones; Greg G. Sass; Ashley Trudeau; Brett T. van Poorten; Dane Whittaker (Fish and Fisheries, 2020)
Recreational fisheries are culturally and economically important around the world. Recent research emphasizes that understanding and managing these systems requires a social–ecological perspective. We systematically reviewed quantitative social–ecological models of marine and freshwater recreational fisheries to summarize their conceptualization of social, ecological, and social–ecological dynamics and identify research frontiers. From a candidate set of 626 studies published between 1975 and 2018, 49 met criteria for inclusion in our review. These studies, though diverse in terms of focal species and processes considered, were geographically limited to a few locations and ignored large regions of the globe where recreational fishing is important. There were also important gaps in the social and ecological processes that were included in published models. Reflecting on these patterns in the context of previous conceptual frameworks, we define five key frontiers for future work: 1) exploring the implications of social and behavioural processes like heuristics, social norms, and information sharing for angler decisions and fishery dynamics; 2) modelling governance with more realistic complexity; 3) incorporating ideas from resilience thinking and complex adaptive systems, including slow variables, destabilizing feedbacks, surprises and diversity; 4) considering key ideas in fisheries systems, including spatial and temporal effort dynamics, catch hyperstability, and stocking; and 5) thinking synthetically about the models that we use to describe social–ecological dynamics in recreational fisheries, via explicit comparisons and formal integration with data. Exploration of these frontiers, while remembering the distinction between model complexity and model usefulness, will improve our ability to understand and sustain recreational fisheries.

Negative frequency‐dependent growth underlies the stable coexistence of two cosmopolitan aquatic plants - David W. Armitage; Stuart E. Jones (Ecology, 2019)
Identifying and quantifying the mechanisms influencing species coexistence remains a major challenge for the study of community ecology. These mechanisms, which stem from species’ differential responses to competition and their environments, promote coexistence if they give each species a growth advantage when rare. Yet despite the widespread assumption that co‐occurring species stably coexist, there have been few empirical demonstrations in support of this claim. Likewise, coexistence is often assumed to result from interspecific differences in life‐history traits, but the relative contributions of these trait differences to coexistence are rarely quantified, particularly across environmental gradients. Using two widely co‐occurring and ecologically similar species of freshwater duckweed plants ( Spirodela polyrhiza and Lemna minor ), we tested hypotheses that interspecific differences in facultative dormancy behaviors, thermal reaction norms, and density‐dependent growth promote coexistence between these species, and that their relative influences on coexistence change as average temperatures and fluctuations around them vary. In competition experiments, we found strong evidence for negative frequency‐dependent growth across a range of both static and fluctuating temperatures, suggesting a critical role of fluctuation‐independent stabilization in coexistence. This negative frequency dependence could be explained by our observation that for both species, intraspecific competition was over 1.5 times stronger than interspecific competition, granting each species a low‐density growth advantage. Using an empirically parameterized competition model, we found that while coexistence was facilitated by environmental fluctuations, fluctuation‐independent stabilization via negative frequency dependence was crucial for coexistence. Conversely, the temporal storage effect, an important fluctuation‐dependent mechanism, was relatively weak in comparison. Contrary to expectations, differences in the species’ thermal reaction norms and dormancy behaviors did not significantly promote coexistence in fluctuating environments. Our results highlight how coexistence in two ubiquitous and ostensibly similar aquatic plants is not necessarily a product of their most obvious interspecific differences, and instead results from subtle niche differences causing negative frequency‐dependent growth, which acts consistently on both species across environmental gradients.

Methane Cycling Contributes to Distinct Patterns in Carbon Stable Isotopes of Wetland Detritus - Julia A. Hart; Carmella Vizza; William E. West; Dominic T. Chaloner; Stuart E. Jones; Gary A. Lamberti (Wetlands, 2019)

A Framework for Understanding Variation in Pelagic Gross Primary Production of Lake Ecosystems - Patrick T. Kelly; Christopher T. Solomon; Jacob A. Zwart; Stuart E. Jones (Ecosystems, 2018)

Crab Burrowing Limits Surface Litter Accumulation in a Temperate Salt Marsh: Implications for Ecosystem Functioning and Connectivity - Jorge L. Gutiérrez; Clive G. Jones; Pablo D. Ribeiro; Stuart E. G. Findlay; Peter M. Groffman (Ecosystems, 2018)

How can wages sustain a living? By getting ahead of the curve - Stuart Colin Carr; Molefe Maleka; Ines Meyer; Marie-Louise Barry; Jarrod Haar; Jane Parker; James Arrowsmith; Christian Yao; Darrin Hodgetts; Harvey Jones; Amanda Young-Hausner; Emeline Afeaki-Mafile’o; et al. (Sustainability Science, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Fish‐Net: Probabilistic models for fishway planning, design and monitoring to support environmentally sustainable hydropower - Martin Wilkes; Lee Baumgartner; Craig Boys; Luiz G M Silva; Justin O'Connor; Matthew Jones; Ivor Stuart; Evelyn Habit; Oscar Link; J Angus Webb (Fish and Fisheries, 2018)
The construction of fishways for upstream and downstream connectivity is the preferred mitigation measure for hydropower dams and other riverine barriers. Yet empirical evidence for effective design criteria for many species is missing. We therefore assembled a group of international fishway designers and combined their knowledge with available empirical data using a formal expert elicitation protocol and Bayesian networks. The expert elicitation method we use minimizes biases typically associated with such approaches. Demonstrating our application with a case‐study on the temperate Southern Hemisphere, we use the resulting probabilistic models to predict the following, given alternative design parameters: (i) the effectiveness of technical fishways for upstream movement of migratory fish; (ii) habitat quality in nature‐like bypasses for resident fish; and (iii) rates of mortality during downstream passage of all fish through turbines and spillways. The Fish Passage Network (Fish‐Net) predicts that fishways for native species could be near 0% or near 100% efficient depending on their design, suggesting great scope for adequate mitigation. Sensitivity analyses revealed the most important parameters as follows: (i) design of attraction and entrance features of technical fishways for upstream migration; (ii) habitat preferences of resident fish in nature‐like bypasses; and (iii) susceptibility of fish to barotrauma and blade strike during turbine passage. Numerical modelling predicted that mortality rates of small‐bodied fish (50–100 mm TL ) due to blade strike may be higher for Kaplan than Francis turbines. Our findings can be used to support environmentally sustainable decisions in the planning, design and monitoring stages of hydropower development.

Landscape patterns shape wetland pond ecosystem function from glacial headwaters to ocean - Carmella Vizza; Jacob A. Zwart; Stuart E. Jones; Scott D. Tiegs; Gary A. Lamberti (Limnology and Oceanography, 2017)
Examining patterns and processes along the aquatic continuum from headwaters to ocean can benefit from a landscape ecology approach, where hydrologic and ecological processes depend on landscape position. We conducted a study of freshwater wetland ponds subject to similar climatic conditions but distributed along a 20‐km trajectory from glacial headwaters to ocean in southcentral Alaska, U.S.A. Specifically, we investigated how proximity to glaciers and ocean influenced physical, chemical, and biological characteristics of ponds. Physicochemical patterns along a distance gradient from the ocean supported the hypothesized influence of elevation and potential atmospheric deposition of marine‐derived nitrogen, whereas those related to glacial flow path length may reflect inputs from glacial weathering. We expected that the effects of landscape and hydrology on physicochemical patterns would provide a template for shaping ecosystem processes, but ecosystem processes also appeared to contribute to physicochemical patterns across this landscape. Ponds more heavily influenced by glaciers tended to be more heterotrophic exhibiting greater rates of organic‐matter decomposition and ecosystem respiration, which were positively correlated with phosphorus and iron concentrations likely due to glacial weathering and remineralization processes. In contrast, ponds near the ocean tended to be more autotrophic exhibiting greater gross primary production and net ecosystem production, processes that may have contributed to greater total nitrogen, nitrogen to phosphorus ratios, and dissolved organic carbon concentrations. Consideration of the relative importance of hydrologic inputs across the landscape is needed because the acceleration of glacial melt and sea‐level rise by climate change may alter future broad‐scale patterns of ecosystem processes.

The Influence of Hydrologic Residence Time on Lake Carbon Cycling Dynamics Following Extreme Precipitation Events - Jacob A. Zwart; Stephen D. Sebestyen; Christopher T. Solomon; Stuart E. Jones (Ecosystems, 2017)

The value of virtual conferencing for ecology and conservation - Hannah Fraser; Kylie Soanes; Stuart A. Jones; Chris S. Jones; Matthew Malishev (Conservation Biology, 2017)
The objectives of conservation science and dissemination of its research create a paradox: Conservation is about preserving the environment, yet scientists spread this message at conferences with heavy carbon footprints. Ecology and conservation science depend on global knowledge exchange—getting the best science to the places it is most needed. However, conference attendance from developed countries typically outweighs that from developing countries that are biodiversity and conservation hotspots. If any branch of science should be trying to maximize participation while minimizing carbon emissions, it is conservation. Virtual conferencing is common in other disciplines, such as education and humanities, but it is surprisingly underused in ecology and conservation. Adopting virtual conferencing entails a number of challenges, including logistics and unified acceptance, which we argue can be overcome through planning and technology. We examined 4 conference models: a pure‐virtual model and 3 hybrid hub‐and‐node models, where hubs stream content to local nodes. These models collectively aim to mitigate the logistical and administrative challenges of global knowledge transfer. Embracing virtual conferencing addresses 2 essential prerequisites of modern conferences: lowering carbon emissions and increasing accessibility for remote, time‐ and resource‐poor researchers, particularly those from developing countries.

Productivity and depth regulate lake contributions to atmospheric methane - William E. West; Kevin P. Creamer; Stuart E. Jones (Limnology and Oceanography, 2016)
Despite significant contributions of inland lakes to the global methane cycle, we lack a process‐based understanding of what regulates inter‐lake variation in methane emissions. Previous comparative work has identified a potential link between lake primary productivity and methane emissions; also, lab‐scale experiments suggest that the addition of algal substrate to anoxic sediments rapidly enhances rates of methanogenesis. This existing work indicates that primary productivity could enhance lake contributions to the global methane cycle. However, a more systematic investigation of the links between lake primary production, methanogenesis, and methane emission to the atmosphere is required to quantify the implications of increased cultural eutrophication for methane evasion from lakes. Using paired measurements of methanogenesis and methane emissions on 16 north temperate lakes, we documented a positive relationship between lake productivity and sediment methanogenesis rates. However, increased methanogenesis rates did not result in an increase in diffusive methane emissions. Rather, they generated greater methane storage during summer stratification and enhanced methane emission to the atmosphere via bubbling (ebullition), dependent on site depth. Ebullition most frequently occurred at sites less than 6 m deep and where methanogenesis rates were high. The relationships between lake productivity, methanogenesis, and depth‐dependent ebullition suggests it is likely that shallow, productive lakes contribute significantly more methane to the atmosphere than deep, clear lakes and will continue to do so in light of the growing prevalence of lake eutrophication.

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

Experimental whole‐lake increase of dissolved organic carbon concentration produces unexpected increase in crustacean zooplankton density - Patrick T. Kelly; Nicola Craig; Christopher T. Solomon; Brian C. Weidel; Jacob A. Zwart; Stuart E. Jones (Global Change Biology, 2016)
The observed pattern of lake browning, or increased terrestrial dissolved organic carbon ( DOC ) concentration, across the northern hemisphere has amplified the importance of understanding how consumer productivity varies with DOC concentration. Results from comparative studies suggest these increased DOC concentrations may reduce crustacean zooplankton productivity due to reductions in resource quality and volume of suitable habitat. Although these spatial comparisons provide an expectation for the response of zooplankton productivity as DOC concentration increases, we still have an incomplete understanding of how zooplankton respond to temporal increases in DOC concentration within a single system. As such, we used a whole‐lake manipulation, in which DOC concentration was increased from 8 to 11 mg L −1 in one basin of a manipulated lake, to test the hypothesis that crustacean zooplankton production should subsequently decrease. In contrast to the spatially derived expectation of sharp DOC ‐mediated decline, we observed a small increase in zooplankton densities in response to our experimental increase in DOC concentration of the treatment basin. This was due to significant increases in gross primary production and resource quality (lower seston carbon‐to‐phosphorus ratio; C:P). These results demonstrate that temporal changes in lake characteristics due to increased DOC may impact zooplankton in ways that differ from those observed in spatial surveys. We also identified significant interannual variability across our study region, which highlights potential difficulty in detecting temporal responses of organism abundances to gradual environmental change (e.g., browning).

Species sorting along a subsidy gradient alters bacterial community stability - Mario E. Muscarella; Stuart E. Jones; Jay T. Lennon (Ecology, 2016)
The movement of resources between terrestrial and aquatic habitats has strong effects on ecological processes in recipient ecosystems. Allochthonous inputs modify the quality and quantity of the available resource pool in ways that may alter the composition and stability of recipient communities. Inputs of terrestrial dissolved organic carbon ( tDOC ) into aquatic ecosystems represent a large influx of resources that has the potential to affect local communities, especially microorganisms. To evaluate the effects of terrestrial inputs on aquatic bacterial community composition and stability, we manipulated the supply rate of tDOC to a set of experimental ponds. Along the tDOC supply gradient, we measured changes in diversity and taxon‐specific changes in relative abundance and activity. We then determined community stability by perturbing each pond using a pulse of inorganic nutrients and measuring changes in composition and activity (i.e., responsiveness) along the gradient. Terrestrial DOC supply significantly altered the composition of the active bacterial community. The composition of the active bacterial community changed via decreases in richness and evenness as well as taxon‐specific changes in relative abundance and activity indicating species sorting along the gradient. Likewise, the responsiveness of the active bacterial community decreased along the gradient, which led to a more stable active community. We did not, however, observe these changes in diversity and stability in the total community (i.e., active and inactive organisms), which suggests that tDOC supply modifies bacterial community stability through functional not structural changes . Together, these results show that altered aquatic terrestrial linkages can have profound effects on the activity and stability of the base of the food web and thus can alter ecosystem functioning.

Migratory diversity predicts population declines in birds - James J. Gilroy; Jennifer A. Gill; Stuart H. M. Butchart; Victoria R. Jones; Aldina M. A. Franco (Ecology Letters, 2016)
Declines in migratory species are a pressing concern worldwide, but the mechanisms underpinning these declines are not fully understood. We hypothesised that species with greater within‐population variability in migratory movements and destinations, here termed ‘migratory diversity’, might be more resilient to environmental change. To test this, we related map‐based metrics of migratory diversity to recent population trends for 340 European breeding birds. Species that occupy larger non‐breeding ranges relative to breeding, a characteristic we term ‘migratory dispersion’, were less likely to be declining than those with more restricted non‐breeding ranges. Species with partial migration strategies (i.e. overlapping breeding and non‐breeding ranges) were also less likely to be declining than full migrants or full residents, an effect that was independent of migration distance. Recent rates of advancement in Europe‐wide spring arrival date were greater for partial migrants than full migrants, suggesting that migratory diversity may also help facilitate species responses to climate change.

Relating belowground microbial composition to the taxonomic, phylogenetic, and functional trait distributions of trees in a tropical forest - Albert Barberán; Krista L. McGuire; Jeffrey A. Wolf; F. Andrew Jones; Stuart Joseph Wright; Benjamin L. Turner; Adam Essene; Stephen P. Hubbell; Brant C. Faircloth; Noah Fierer (Ecology Letters, 2015)
The complexities of the relationships between plant and soil microbial communities remain unresolved. We determined the associations between plant aboveground and belowground (root) distributions and the communities of soil fungi and bacteria found across a diverse tropical forest plot. Soil microbial community composition was correlated with the taxonomic and phylogenetic structure of the aboveground plant assemblages even after controlling for differences in soil characteristics, but these relationships were stronger for fungi than for bacteria. In contrast to expectations, the species composition of roots in our soil core samples was a poor predictor of microbial community composition perhaps due to the patchy, ephemeral, and highly overlapping nature of fine root distributions. Our ability to predict soil microbial composition was not improved by incorporating information on plant functional traits suggesting that the most commonly measured plant traits are not particularly useful for predicting the plot‐level variability in belowground microbial communities.

Habitat, not resource availability, limits consumer production in lake ecosystems - Nicola Craig; Stuart E. Jones; Brian C. Weidel; Christopher T. Solomon (Limnology and Oceanography, 2015)
Food web productivity in lakes can be limited by dissolved organic carbon (DOC), which reduces fish production by limiting the abundance of their zoobenthic prey. We demonstrate that in a set of 10 small, north temperate lakes spanning a wide DOC gradient, these negative effects of high DOC concentrations on zoobenthos production are driven primarily by availability of warm, well‐oxygenated habitat, rather than by light limitation of benthic primary production as previously proposed. There was no significant effect of benthic primary production on zoobenthos production after controlling for oxygen, even though stable isotope analysis indicated that zoobenthos do use this resource. Mean whole‐lake zoobenthos production was lower in high‐DOC lakes with reduced availability of oxygenated habitat, as was fish biomass. These insights improve understanding of lake food webs and inform management in the face of spatial variability and ongoing temporal change in lake DOC concentrations.

Blastocyst genotyping for quality control of mouse mutant archives: an ethical and economical approach - Ferdinando Scavizzi; Edward Ryder; Stuart Newman; Marcello Raspa; Diane Gleeson; Hannah Wardle-Jones; Lluis Montoliu; Almudena Fernandez; Marie-Laure Dessain; Vanessa Larrigaldie; Zuzana Khorshidi; Reetta Vuolteenaho; et al. (Transgenic Research, 2015)

Phytoplankton traits predict ecosystem function in a global set of lakes - Jacob A. Zwart; Christopher T. Solomon; Stuart E. Jones (Ecology, 2015)
Predicting ecosystem function from environmental conditions is a central goal of ecosystem ecology. However, many traditional ecosystem models are tailored for specific regions or ecosystem types, requiring several regional models to predict the same function. Alternatively, trait‐based approaches have been effectively used to predict community structure in both terrestrial and aquatic environments and ecosystem function in a limited number of terrestrial examples. Here, we test the efficacy of a trait‐based model in predicting gross primary production (GPP) in lake ecosystems. We incorporated data from >1000 United States lakes along with laboratory‐generated phytoplankton trait data to build a trait‐based model of GPP and then validated the model with GPP observations from a separate set of globally distributed lakes. The trait‐based model performed as well as or outperformed two ecosystem models both spatially and temporally, demonstrating the efficacy of trait‐based models for predicting ecosystem function over a range of environmental conditions.

Thalamocortical neurons display suppressed burst-firing due to an enhanced Ih current in a genetic model of absence epilepsy - Stuart M. Cain; John R. Tyson; Karen L. Jones; Terrance P. Snutch (Pflügers Archiv - European Journal of Physiology, 2015)

A test of the subsidy–stability hypothesis: the effects of terrestrial carbon in aquatic ecosystems - Stuart E. Jones; Jay T. Lennon (Ecology, 2015)
Global change is altering the movement of materials across landscapes in ways that likely have major consequences for the functioning and stability of ecosystems. For example, the export of dissolved organic carbon (DOC) from terrestrial to aquatic ecosystems is increasing globally. This browning phenomenon is expected to alter the stability of recipient aquatic ecosystems, but theory provides contrasting predictions about the form and direction of this response. We created a gradient in terrestrial DOC supply by adding humic substances on weekly basis to 10 experimental ponds (10 6 L each) over a growing season. The manipulation of terrestrial DOC supply had strong effects on the chemical, physical, and biological properties of the pond ecosystems. Light attenuation linearly increased with terrestrial DOC supply, which created a shading effect that negatively influenced whole‐pond gross primary production and respiration. Despite this, bacterial contributions to basal energy mobilization and respiration increased with terrestrial DOC supply indicating that aquatic food webs were subsidized by terrestrial inputs. After establishing the DOC gradient, we used dynamic linear models to test the subsidy–stability hypothesis by measuring the resilience and sensitivity of each pond to a pulse nutrient perturbation. We found that recovery from the perturbation decreased nonlinearly along a gradient in terrestrial DOC supply. Reciprocal transplant experiments indicated that owing primarily to its light attenuating properties and recalcitrant nature, terrestrial DOC diminished aquatic ecosystem stability by reducing nutrient turnover rates (NTR). Together, our results demonstrate that global‐change‐mediated alterations in the movement of material and energy between habitats can have unpredictable and dramatic impacts on the reliability of ecosystem services.

Ecosystem Consequences of Changing Inputs of Terrestrial Dissolved Organic Matter to Lakes: Current Knowledge and Future Challenges - Christopher T. Solomon; Stuart E. Jones; Brian C. Weidel; Ishi Buffam; Megan L. Fork; Jan Karlsson; Søren Larsen; Jay T. Lennon; Jordan S. Read; Steven Sadro; Jasmine E. Saros (Ecosystems, 2015)

Dissolved organic carbon concentration controls benthic primary production: Results from in situ chambers in north‐temperate lakes - Sean C. Godwin; Stuart E. Jones; Brian C. Weidel; Christopher T. Solomon (Limnology and Oceanography, 2014)
We evaluated several potential drivers of primary production by benthic algae (periphyton) in north‐temperate lakes. We used continuous dissolved oxygen measurements from in situ benthic chambers to quantify primary production by periphyton at multiple depths across 11 lakes encompassing a broad range of dissolved organic carbon (DOC) and total phosphorous (TP) concentrations. Light‐use efficiency (primary production per unit incident light) was inversely related to average light availability (% of surface light) in 7 of the 11 study lakes, indicating that benthic algal assemblages exhibit photoadaptation, likely through physiological or compositional changes. DOC alone explained 86% of the variability in log‐transformed whole‐lake benthic production rates. TP was not an important driver of benthic production via its effects on nutrient and light availability. This result is contrary to studies in other systems, but may be common in relatively pristine north‐temperate lakes. Our simple empirical model may allow for the prediction of whole‐lake benthic primary production from easily obtained measurements of DOC concentration.

Terrestrial carbon is a resource, but not a subsidy, for lake zooplankton - Patrick T. Kelly; Christopher T. Solomon; Brian C. Weidel; Stuart E. Jones (Ecology, 2014)
Inputs of terrestrial organic carbon (t‐OC) into lakes are often considered a resource subsidy for aquatic consumer production. Although there is evidence that terrestrial carbon can be incorporated into the tissues of aquatic consumers, its ability to enhance consumer production has been debated. Our research aims to evaluate the net effect of t‐OC input on zooplankton. We used a survey of zooplankton production and resource use in ten lakes along a naturally occurring gradient of t‐OC concentration to address these questions. Total and group‐specific zooplankton production was negatively related to t‐OC. Residual variation in zooplankton production that was not explained by t‐OC was negatively related to terrestrial resource use (allochthony) by zooplankton. These results challenge the designation of terrestrial carbon as a resource subsidy; rather, the negative effect of reduced light penetration on the amount of suitable habitat and the low resource quality of t‐OC appear to diminish zooplankton production. Our findings suggest that ongoing continental‐scale increases in t‐OC concentrations of lakes will likely have negative impacts on the productivity of aquatic food webs.

Freshwater bacterial lifestyles inferred from comparative genomics - Joshua A. Livermore; Scott J. Emrich; John Tan; Stuart E. Jones (Environmental Microbiology, 2014)
Summary While micro‐organisms actively mediate and participate in freshwater ecosystem services, we know little about freshwater microbial genetic diversity. Genome sequences are available for many bacteria from the human microbiome and the ocean (over 800 and 200, respectively), but only two freshwater genomes are currently available: the streamlined genomes of Polynucleobacter necessarius ssp . asymbioticus and the Actinobacterium AcI ‐ B 1. Here, we sequenced and analysed draft genomes of eight phylogentically diverse freshwater bacteria exhibiting a range of lifestyle characteristics. Comparative genomics of these bacteria reveals putative freshwater bacterial lifestyles based on differences in predicted growth rate, capability to respond to environmental stimuli and diversity of useable carbon substrates. Our conceptual model based on these genomic characteristics provides a foundation on which further ecophysiological and genomic studies can be built. In addition, these genomes greatly expand the diversity of existing genomic context for future studies on the ecology and genetics of freshwater bacteria.

Rapid conversion of EUCOMM/KOMP-CSD alleles in mouse embryos using a cell-permeable Cre recombinase - Edward Ryder; Brendan Doe; Diane Gleeson; Richard Houghton; Priya Dalvi; Evelyn Grau; Bishoy Habib; Evelina Miklejewska; Stuart Newman; Debarati Sethi; Caroline Sinclair; Sapna Vyas; et al. (Transgenic Research, 2014)

Transcriptomics of coping strategies in free‐swimming Lepeophtheirus salmonis (Copepoda) larvae responding to abiotic stress - Ben J. G. Sutherland; Stuart G. Jantzen; Motoshige Yasuike; Dan S. Sanderson; Ben F. Koop; Simon R. M. Jones (Molecular Ecology, 2012)
The salmon louse Lepeophtheirus salmonis is a marine ectoparasite of wild and farmed salmon in the Northern Hemisphere. Infections of farmed salmon are of economic and ecological concern. Nauplius and copepodid salmon lice larvae are free‐swimming and disperse in the water column until they encounter a host. In this study, we characterized the sublethal stress responses of L. salmonis copepodid larvae by applying a 38K oligonucleotide microarray to profile transcriptomes following 24 h exposures to suboptimal salinity (30–10 parts per thousand ( ‰ )) or temperature (16–4 °C) environments. Hyposalinity exposure resulted in large‐scale gene expression changes relative to those elicited by a thermal gradient. Subsequently, transcriptome responses to a more finely resolved salinity gradient between 30 ‰ and 25 ‰ were profiled. Minimal changes occurred at 29 ‰ or 28 ‰ , a threshold of response was identified at 27 ‰ , and the largest response was at 25 ‰. Differentially expressed genes were clustered by pattern of expression, and clusters were characterized by functional enrichment analysis. Results indicate larval copepods adopt two distinct coping strategies in response to short‐term hyposaline stress: a primary response using molecular chaperones and catabolic processes at 27 ‰ ; and a secondary response up‐regulating ion pumps, transporters, a different suite of chaperones and apoptosis‐related transcripts at 26 ‰ and 25 ‰ . The results further our understanding of the tolerances of L. salmonis copepodids to salinity and temperature gradients and may assist in the development of salmon louse management strategies.

Pharmacokinetic Evaluation of Intranasally Administered Vinyl Polymer-Coated Lorazepam Microparticles in Rabbits - Yanjun Zhao; Marc B. Brown; Rajeshree H. Khengar; Matthew J. Traynor; Pedro Barata; Stuart A. Jones (The AAPS Journal, 2012)

Genomic Resources for Sea Lice: Analysis of ESTs and Mitochondrial Genomes - Motoshige Yasuike; Jong Leong; Stuart G. Jantzen; Kristian R. von Schalburg; Frank Nilsen; Simon R. M. Jones; Ben F. Koop (Marine Biotechnology, 2012)

Population trends in the Slavonian grebe Podiceps auritus (L.) and Chironomidae (Diptera) at a Scottish loch - Stephen J. Brooks; Vivienne J. Jones; Richard J. Telford; Peter G. Appleby; Emily Watson; Suzanne McGowan; Stuart Benn (Journal of Paleolimnology, 2012)

Reconstructing recent sedimentation in two urbanised coastal lagoons (NSW, Australia) using radioisotopes and geochemistry - Suzanne E. Hollins; Jennifer J. Harrison; Brian G. Jones; Atun Zawadzki; Henk Heijnis; Stuart Hankin (Journal of Paleolimnology, 2011)

Evidence for structuring of bacterial community composition by organic carbon source in temperate lakes - Stuart E. Jones; Ryan J. Newton; Katherine D. McMahon (Environmental Microbiology, 2009)
Summary Water entering lakes from the surrounding watershed often delivers large amounts of terrestrial‐derived dissolved organic carbon (DOC) that can contribute to aquatic bacterial production. However, research suggests that phytoplankton‐derived DOC is more labile than its terrestrial counterpart, owing to microbial processing of terrestrial‐derived DOC along its flow path to surface waters. The ratio of water colour (absorbance at 440 nm) to chlorophyll a has been suggested as a simple measure of the relative contribution of terrestrial and aquatic primary production to aquatic secondary production. To explore the correlation between primary DOC source and the occurrence of bacterial taxonomic groups, we conducted a survey of bacterial 16S rRNA gene composition in 15 lakes positioned along a water colour : chlorophyll a gradient. Our goal was to identify bacterial taxa occurrence patterns along the colour : chlorophyll a gradient that may indicate a competitive advantage for bacterial taxa using terrestrial or aquatic carbon. We observed a large number of bacterial taxa occurrence patterns suggestive of carbon substrate niche partitioning, especially when relatively highly resolved taxonomic groups were considered. Our survey supports the hypothesis that bacterial taxa partition along a carbon substrate source gradient and highlights carbon source–bacterial interactions that should be explored further.

Species‐sorting may explain an apparent minimal effect of immigration on freshwater bacterial community dynamics - Stuart E. Jones; Katherine D. McMahon (Environmental Microbiology, 2009)
Summary Long distance atmospheric transport of bacterial cells is often implied as a driver of the apparent cosmopolitan distribution of bacterial taxa. Surprisingly, efforts to measure immigration in bacterial communities are rare. An 8‐week time series of within‐lake bacterial community composition and atmospheric deposition rates and composition were used to estimate the influence of immigration on bacterial community dynamics in two north temperate lakes. Characterization of bacterial community dynamics using automated ribosomal intergenic spacer analysis suggested moderate overlap in composition between the lakes and atmospherically deposited cells. However, taxa that appeared to be delivered by atmospheric deposition had a relatively minor influence on lake bacterial community dynamics. The weak influence of immigrating bacterial taxa suggests that a species‐sorting concept best describes aquatic bacterial metacommunity dynamics.

Local Participation in Natural Resource Monitoring: a Characterization of Approaches - FINN DANIELSEN; NEIL D. BURGESS; ANDREW BALMFORD; PAUL F. DONALD; MIKKEL FUNDER; JULIA P. G. JONES; PHILIP ALVIOLA; DANILO S. BALETE; TOM BLOMLEY; JUSTIN BRASHARES; BRIAN CHILD; MARTIN ENGHOFF; et al. (Conservation Biology, 2009)
The monitoring of trends in the status of species or habitats is routine in developed countries, where it is funded by the state or large nongovernmental organizations and often involves large numbers of skilled amateur volunteers. Far less monitoring of natural resources takes place in developing countries, where state agencies have small budgets, there are fewer skilled professionals or amateurs, and socioeconomic conditions prevent development of a culture of volunteerism. The resulting lack of knowledge about trends in species and habitats presents a serious challenge for detecting, understanding, and reversing declines in natural resource values. International environmental agreements require signatories undertake systematic monitoring of their natural resources, but no system exists to guide the development and expansion of monitoring schemes. To help develop such a protocol, we suggest a typology of monitoring categories, defined by their degree of local participation, ranging from no local involvement with monitoring undertaken by professional researchers to an entirely local effort with monitoring undertaken by local people. We assessed the strengths and weaknesses of each monitoring category and the potential of each to be sustainable in developed or developing countries. Locally based monitoring is particularly relevant in developing countries, where it can lead to rapid decisions to solve the key threats affecting natural resources, can empower local communities to better manage their resources, and can refine sustainable‐use strategies to improve local livelihoods. Nevertheless, we recognize that the accuracy and precision of the monitoring undertaken by local communities in different situations needs further study and field protocols need to be further developed to get the best from the unrealized potential of this approach. A challenge to conservation biologists is to identify and establish the monitoring system most relevant to a particular situation and to develop methods to integrate outputs from across the spectrum of monitoring schemes to produce wider indices of natural resources that capture the strengths of each.

Influence of typhoons on annual CO 2 flux from a subtropical, humic lake - STUART E. JONES; TIMOTHY K. KRATZ; CHIH‐YU CHIU; KATHERINE D. McMAHON (Global Change Biology, 2009)
The Intergovernmental Panel on Climate Change predicts dramatic changes in precipitation patterns over the next century. One potential method for inferring how these changes in annual precipitation and intensity of storm events will influence aquatic ecosystems is to study and model present‐day lakes that share climatic characteristics with future climate scenarios. A small lake in north‐central Taiwan provided an excellent opportunity to explore the influence of intense meteorological events on CO 2 exchange between surface waters and the atmosphere. Each year Yuan Yang Lake (YYL) is influenced by multiple typhoons that pass near the island of Taiwan. This lake has been instrumented with a sensor network that monitors water column and meteorological parameters at a high temporal resolution (2–10 min intervals). Using this high‐resolution data and manually collected CO 2 samples, a mass‐balance model of CO 2 dynamics in YYL was developed. In addition, a generalized simulation model was used to explore how typhoon frequency, intensity, and timing impact CO 2 efflux to the atmosphere. Our findings suggest that increased annual precipitation and frequency of storm events results in greater epilimnetic interaction with the watershed and hypolimnion. These interactions resulted in elevated epilimetic CO 2 concentrations and therefore greater evasion of CO 2 to the atmosphere.

Manipulation of Corticosteroid Release from a Transiently Supersaturated Topical Metered Dose Aerosol Using A Residual Miscible Co-Solvent - Monica L. Reid; Marc B. Brown; Stuart A. Jones (Pharmaceutical Research, 2008)

Typhoons initiate predictable change in aquatic bacterial communities - Stuart E. Jones; Chih-Yu Chiu; Timothy K. Kratz; Jiunn-Tzong Wu; Ashley Shade; Katherine D. McMahon (Limnology and Oceanography, 2008)
We explored patterns of change in bacterioplankton and phytoplankton community composition in response to typhoons in a subtropical, subalpine freshwater humic lake in Taiwan. Thermal profiles with depth, nearsurface dissolved oxygen, and meteorological conditions were measured at high temporal resolution using an instrumented buoy. We collected samples across a time series spanning two typhoon seasons and assessed bacterial community composition at each time point using a fingerprinting technique targeting the internal transcribed spacer region of the ribosomal RNA operon. Wind and rain associated with the typhoons mixed the otherwise stably stratified water column. After each of six typhoon‐induced mixing events, the bacterial community composition was reset to similar conditions, revealing a surprisingly deterministic pattern of recovery that was reminiscent of secondary succession following large infrequent disturbances in terrestrial ecosystems. Distinct bacterial assemblages were associated with epilimnion and hypolimnion samples collected more than 80 d after a mixing event. These assemblages were also distinct from the communities observed in the generally unstratified water column within 7 d after a typhoon. Our results were surprising since bacterial communities are not expected to respond in such predictable ways because of their immense complexity and diversity. In contrast, phytoplankton communities did not recover in a predictable way after typhoons.

The influence of habitat heterogeneity on freshwater bacterial community composition and dynamics - Ashley Shade; Stuart E. Jones; Katherine D. McMahon (Environmental Microbiology, 2008)
Summary Multiple forces structure natural microbial communities, but the relative roles and interactions of these drivers are poorly understood. Gradients of physical and chemical parameters can be especially influential. In traditional ecological theory, variability in environmental conditions across space and time represents habitat heterogeneity, which may shape communities. Here we used aquatic microbial communities as a model to investigate the relationship between habitat heterogeneity and community composition and dynamics. We defined spatial habitat heterogeneity as vertical temperature and dissolved oxygen (DO) gradients in the water column, and temporal habitat heterogeneity as variation throughout the open‐water season in these environmental parameters. Seasonal lake mixing events contribute to temporal habitat heterogeneity by destroying and re‐creating these gradients. Because of this, we selected three lakes along a range of annual mixing frequency (polymictic, dimictic, meromictic) for our study. We found that bacterial community composition (BCC) was distinct between the epilimnion and hypolimnion within stratified lakes, and also more variable within the epilimnia through time. We found stark differences in patterns of epilimnion and hypolimnion dynamics over time and across lakes, suggesting that specific drivers have distinct relative importance for each community.

Regulated floodplains – a trap for unwary fish - M. J. JONES; I. G. STUART (Fisheries Management and Ecology, 2008)
Loss of river‐floodplain (lateral) connectivity has impacted on fish communities and fisheries around the world. However, evidence of the impacts of reduced lateral connectivity on Australian native fish remains scant. To document these impacts, isolated pools located immediately downstream of two major regulators (or weirs) that control flows from the Murray River to an extensive off‐stream floodplain, were pumped out five times between 2001 and 2006. A total of 20 980 fish (16 228 native, 4752 non‐native) comprising 15 species (five non‐native) were collected. Five fish species collected are classified as threatened, while turtles and macroinvertebrates were also present. Regulator operation appeared to affect the number of fish becoming stranded, with the highest number coinciding with longer regulator openings and extended floodplain inundation. Hundreds of floodplain regulators exist on Australian rivers, and all have the potential to impact upon native fish. Trial of several potential management and engineering solutions is recommended to improve river–floodplain connectivity in lowland rivers.

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Interannual dynamics and phenology of bacterial communities in a eutrophic lake - Ashley Shade; Angela D. Kent; Stuart E. Jones; Ryan J. Newton; Eric W. Triplett; Katherine D. McMahon (Limnology and Oceanography, 2007)
We investigated patterns of intra‐ and interannual change in pelagic bacterial community composition (BCC, assessed using automated ribosomal intergenic spacer analysis) over six years in eutrophic Lake Mendota, Wisconsin. A regular phenology was repeated across years, implying that freshwater bacterial communities are more predictable in their dynamics than previously thought. Seasonal events, such as water column mixing and trends in water temperature, were most strongly related to BCC variation. Communities became progressively less similar across years between the months of May and September, when the lake was thermally stratified. Dissolved oxygen and nitrate + nitrite concentrations were highly correlated to BCC change within and across seasons. The relationship between BCC and seasonal drivers suggests that trajectories of community change observed over long time series will reflect large‐scale climate variation.

Investigating the scale of structural controls on chlorinated hydrocarbon distributions in the fractured-porous unsaturated zone of a sandstone aquifer in the UK - Adrian Lawrence; Marianne Stuart; Colin Cheney; Neil Jones; Richard Moss (Hydrogeology Journal, 2006)

Movement of common carp, Cyprinus carpio , in a regulated lowland Australian river: implications for management - I. G. STUART; M. J. JONES (Fisheries Management and Ecology, 2006)
Introduced common carp, Cyprinus carpio L., is the most abundant large fish in the Murray‐Darling Basin and past studies have considered it non‐migratory. Movement information is, however, important for targeting control efforts to appropriate habitats and spatial scales. Movement patterns of common carp in the Murray River were investigated between November 1999 and August 2001. In total, 3337 common carp were boat electric fished and externally tagged. Of the 293 (8.8%) fish recaptured, up to 1898 days later, the majority (80%) moved

Experimental manipulations of microbial food web interactions in a humic lake: shifting biological drivers of bacterial community structure - Angela D. Kent; Stuart E. Jones; George H. Lauster; James M. Graham; Ryan J. Newton; Katherine D. McMahon (Environmental Microbiology, 2006)
Summary A previous multiyear study observed correlations between bacterioplankton community composition (BCC) and abundance and the dynamics of phytoplankton populations and bacterivorous grazers in a humic lake. These observations generated hypotheses about the importance of trophic interactions (both top‐down and bottom‐up) for structuring bacterial communities in this lake, which were tested using two multifactorial food web manipulation experiments that separately manipulated the intensity of grazing and the composition of the phytoplankton community. Our results, combined with field observations, suggest that a hierarchy of drivers structures bacterial communities in this lake. While other studies have noted links between aggregate measures of phytoplankton and bacterioplankton communities, we demonstrate here correlations between succession of phytoplankton assemblages and BCC as assessed by automated ribosomal intergenic spacer analysis (ARISA). We used a novel approach linking community ARISA data to phylogenetic assignments from sequence analysis of 16S rRNA gene clone libraries to examine the responses of specific bacterial phylotypes to the experimental manipulations. The synchronous dynamics of these populations suggests that primary producers may mediate BCC and diversity through labile organic matter production, which evolves in quality and quantity during phytoplankton succession. Superimposed on this resource‐mediated control of BCC are brief periods of intense bacterivory that impact bacterial abundance and composition.

The Contribution of Crab Burrow Excavation to Carbon Availability in Surficial Salt-marsh Sediments - Jorge L. Gutiérrez; Clive G. Jones; Peter M. Groffman; Stuart E. G. Findlay; Oscar O. Iribarne; Pablo D. Ribeiro; C. Martín Bruschetti (Ecosystems, 2006)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

Effects of water loss on primary production: A landscape-scale model - Emily H. Stanley; Stuart G. Fisher; Jeremy B. Jones, Jr. (Aquatic Sciences, 2004)

Effects of habitat change and geographical variation on the bird communities of two Indonesian islands - Martin J. Jones; Stuart J. Marsden; Mark D. Linsley (Biodiversity and Conservation, 2003)

Atmospheric motion systems that influence the redistribution and accumulation of insects on the beaches of the Great Lakes in North America - Scott A. Isard; David A. R. Kristovich; Stuart H. Gage; Carl J. Jones; Neil F. Laird (Aerobiologia, 2001)

Isolation and characterization of microsatellite loci in the freshwater gastropod, Biomphalaria glabrata , an intermediate host for Schistosoma mansoni - Catherine S. Jones; Anne E. Lockyer; David Rollinson; Stuart B. Piertney; Leslie R. Noble (Molecular Ecology, 1999)

Characterization of two class I genes from the H2-M region: evidence for a new subfamily - S. R. Arepalli; Elsy P. Jones; T. Kevin Howcroft; Irene Carlo; C.-R. Wang; K. Fischer Lindahl; Dinah S. Singer; Stuart Rudikoff (Immunogenetics, 1998)

Material Spiraling in Stream Corridors: A Telescoping Ecosystem Model - Stuart G. Fisher; Nancy B. Grimm; Eugènia Martí; Robert M. Holmes; Jeremy B. Jones, Jr. (Ecosystems, 1998)

The mouse Chromosome 7 distal imprinting domain maps to G-bands F4/F5 - Colin V. Beechey; Simon T. Ball; K. M. Stuart Townsend; Janet Jones (Mammalian Genome, 1997)

The relative contribution of individual polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzo-p-furans (PCDFs) to toxic equivalent values derived for bulked human adipose tissue samples from Wales, United Kingdom - Raquel Duarte-Davidson; Stuart J. Harrad; Susan Allen; Andrew S. Sewart; Kevin C. Jones (Archives of Environmental Contamination and Toxicology, 1993)